1993
DOI: 10.1002/ppul.1950150608
|View full text |Cite
|
Sign up to set email alerts
|

Forced expiratory flows and lung volumes in normal infants

Abstract: Forced expiratory flows at functional residual capacity (VmaxFRC) by the rapid compression technique and functional residual capacity (FRC) by the helium dilution technique were assessed in 112 normal infants with a mean age of 10.7 months (range, 1.0-31.0). In predicting FRC, log transformation was appropriate and body length was the best predicator. For VmaxFRC, age was a better predictor than length, and logarithmic transformation was not required. In(FRC) = -5.465 + 2.49 x In(length) SD = 0.178; r2 = 0.83 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 18 publications
3
42
0
2
Order By: Relevance
“…Male infants wheeze more frequently than female infants [26±28] and this has been explained by male infants having smaller airways relative to lung size in comparison to females [29,30]. Some demonstrate that a particular sex has higher flows in comparison to the other sex [15,31], whilst other investigators have not observed any difference between male and female infants [12,32,33]. The current authors found that, at the age of 1 and 6 months, males who never wheezed had lower flows than females who never wheezed.…”
Section: Discussionmentioning
confidence: 92%
“…Male infants wheeze more frequently than female infants [26±28] and this has been explained by male infants having smaller airways relative to lung size in comparison to females [29,30]. Some demonstrate that a particular sex has higher flows in comparison to the other sex [15,31], whilst other investigators have not observed any difference between male and female infants [12,32,33]. The current authors found that, at the age of 1 and 6 months, males who never wheezed had lower flows than females who never wheezed.…”
Section: Discussionmentioning
confidence: 92%
“…When adjusted for age, boys had higher alveolar volumes; however, this age-related difference could be accounted for by the greater somatic size of boys than girls. Previous studies of lung volumes in infants and toddlers also found no sex differences when volumes are adjusted for body size (14,15). Our physiologic data is also consistent with morphometric data of autopsied lungs, which found no sex differences from subjects less than 2 years of age (2).…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary first approach, data from 279 infants studied by TEPPER et al [8], and STOCKS and coworkers [19,20], including some delivered prematurely, have been pooled. No interlaboratory differences were detected in the relationship between V'max,FRC and age or body size, although the majority of the younger and preterm infants were studied in London, UK by STOCKS and coworkers [19,20] and the majority of the older infants were studied by TEPPER et al [8] [8,19,20].)…”
Section: Appendix: Reference Datamentioning
confidence: 99%
“…No interlaboratory differences were detected in the relationship between V'max,FRC and age or body size, although the majority of the younger and preterm infants were studied in London, UK by STOCKS and coworkers [19,20] and the majority of the older infants were studied by TEPPER et al [8] [8,19,20].) postnatal age (taking gestational age into account) -4±139 weeks (term was taken to be 40 weeks gestational age) and crown-heel length 40±90 cm.…”
Section: Appendix: Reference Datamentioning
confidence: 99%